Neznano in pozabljeno iz 18. stoletja na Slovenskem - Preinfalk, Miha (ZRC SAZU, Založba ZRC, 2011)
Neznano in pozabljeno iz 18. stoletja na Slovenskem [The Unknown and Forgotten from the 18th-Century Slovenian Territory] is the first monograph written by the Slovenian Society of 18th Century Studies and presents the less known phenomena and aspects of the 18th-century Slovenian territory. The monograph was compiled by twenty-three Slovenian and international authors whose contributions discuss numerous areas spanning general, cultural, music, art and literary history. It is divided into several chapters. The introduction, containing the presentation of the Slovenian provinces in the 18th century, serves as the basic starting point and is followed by chapters "Pravna, upravna in cerkvena zgodovina" ["Legal, Administrative and Ecclesiastical History"], "Umetnost in obrt" ["Art and Crafts"], "Kulturna in socialna zgodovina" ["Cultural and Social History"] and "Jezikoslovje" ["Linguistics"]. The monograph, which was published in digital form, is also distinguished by rich pictorial content.